TOUR de JNP, KEJUARAAN TAHUNAN WISATA OLAH RAGA TANTANGAN PERAIRAN ANTAR DUA TAMAN NASIONAL (Inovasi Strategi Promosi Ekowisata Provinsi Jambi) - Ardi Novra (Pusat Studi Pariwisata Universitas Gadjah Mada, 2012)
Ecotourism activities have been expanding rapidly over the past two decades world-wide and further growth is expected in the future. Efforts to better understand ecotourism, as well as to improve its planning, management and marketing techniques have been conducted by many ecotourism companies and practitioners, governments and research people throughout the world.This paper is specifically concerned with the effort of the local government of Jambi to take the optimally benefit from natural tourism development more competitive. Tour de JNP (tour the Jambi National Park) is an international annual event of territorial water challenge sport-tourism to tracing river stream between Kerinci Seblat and Berbak Na-tional Park. Both national parks represent conservations area owning properties of natu-ral tourism object which offer biodiversities. During tracing streams of Batanghari River, all participants can enjoy the esthetics value of the natural were a view of nature, air freshness and see various history and settlement of traditional cultural society. Pursuant to stream type and deepness of river which vary, hence the setting of champi-onship using boat type different to each phase, and will be divided on 10 phases. Entire phase will be gone through by participant by using boat type differ that is rubber boat, traditional boat of Jambi (Bidar and Kajang Lako), dragon boat, bamboo raft, and sailboat for sea and river. During race of participant will pass some tourism object were Kerinci Lake, Geo-Park, Victoria Brigde, mausoleum of Orang Kayo Hitam, Muaro Jambi Temple, Angso Duo as an eldest traditional market, Tanggo Rajo as a popular man-made tourism object, traditional settlement as long as river, Berhala Island, blackly sand of coastal area, and end in Simpang Malaka a gathering places to drinking wilds animal on the Berbak National Park.